How does Mathematics Shape the Physical Reality? A Journey with some Equations - Adhikari, Rabindra (Journal of Contemporary Review, 2024)
If the universe has its own language, then it is not other than mathematics. This language of mathematics is expressed through the relationship of meaningful symbols. The symbol may differ, but the relationship between them is universal. Instead of considering this language as simply an abstract, this article will examine the beauty beneath the foundation of physical reality. We will reveal some stories about mathematical equations that are considered the most beautiful and fundamental, and elaborate on how they impact the arts, science, technology, and our understanding of the universe. Lastly, we will discuss how these powerful formulas represent the relationship between abstract concepts and the real world so that the ideas of mathematics will never be obsolete.